2012
DOI: 10.1371/journal.pmed.1001313
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Ready-to-Use Supplementary Food to a General Food Distribution on Child Nutritional Status and Morbidity: A Cluster-Randomized Controlled Trial

Abstract: Lieven Huybregts and colleagues investigate how supplementing a general food distribution with a fortified lipid-based spread during a seasonal hunger gap in Chad affects anthropometric and morbidity outcomes for children aged 6 to 36 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 46 publications
6
71
2
3
Order By: Relevance
“…In that study of 840 children, daily provision of 54 g LNS (containing the same amount of Fe as the LNS used in the present study, 6 mg) did not increase malaria or respiratory morbidity (13) . Similar findings have been reported in previous studies that used LNS (11,12) or MNP (3)(4)(5) . In our study, although we LNS, lipid-based nutrient supplement; IRR, incidence rate ratio; ARI, acute respiratory infection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In that study of 840 children, daily provision of 54 g LNS (containing the same amount of Fe as the LNS used in the present study, 6 mg) did not increase malaria or respiratory morbidity (13) . Similar findings have been reported in previous studies that used LNS (11,12) or MNP (3)(4)(5) . In our study, although we LNS, lipid-based nutrient supplement; IRR, incidence rate ratio; ARI, acute respiratory infection.…”
Section: Discussionsupporting
confidence: 91%
“…However, Malawi provides a free national health-care system in public health facilities where most of our participants were treated, and we did not reimburse transport for non-scheduled visits. A study in children aged 6-36 months in Chad (12) recorded an incidence of reported disease episodes of 1·17 per child-month (or 14·04 per child-year) which is close to our findings, suggesting that the high disease incidence at home visits was a true observation. Thus, we believe our results are still valid and representative of the target population, suggesting that 10 and 20 g LNS/d did not increase morbidity in our population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While both groups received improved water storage, one group was randomly assigned an additional water treatment intervention where team members were uncertain whether this additional intervention would add value or not. Another example is a study in Chad by Huybregts et al (2012) which compared a general food distribution programme and ready-to-use supplementary food with a general food distribution (see Table A1 in the Appendix).…”
Section: The Emergency Relief Phasementioning
confidence: 99%
“…The quality of the RCTs (n=8) was evaluated based on the CASP RCT Checklist. Four of these studies were assessed to be of high quality (Bahwere et al, 2014;Karakochuk et al, 2012;Matilsky et al, 2009;Oakley et al, 2010) and four were assessed to be of medium quality (Ciliberto et al, 2005;Huybregts et al, 2012;Isanaka et al, 2009;Maust et al, 2015). The qualitative component of the mixed methods studies (n=2) was evaluated based on the CASP Qualitative Checklist and was assessed to be of medium quality (Belachew and Nekatibeb, 2007;Flax et al, 2009).…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%